ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGELOLA KEUANGAN DAERAH PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KOTA PALU - Rahmah, Nur Athiyah (Katalogis, 2016)
The purpose of this study to determine and analyze factors include individual factors, leadership, systems, team and contextual influence on the performance of regional financial manager at regional work units in Palu City. The results of the analysis of hypothesis testing showed a direct effect positive and significant correlation of factors between the individual, leadership, teams, systems and contextual to the performance of a financial management area on the sectors in Palu city, with correlation coefficients (Multiple R) = 0.835 means that the observed variables have a strong relationship with the dependent variable. While the coefficient of determination (Adjust R Square) of 0.685, which means that 68.5% of the independent variables are able to explain the dependent variable, while 31.5% is influenced by other variables in this study.Â